ANALISIS PENERAPAN MANAJEMEN CORPORATE SOCIAL RESPONSIBILITY (CSR) DI RUMAH SAKIT TK.II PELAMONIA MAKASSAR TAHUN 2022 - Sudirman Hatuina; Dian Ekawaty; Mohammad Ardani Samad; Ryryn Suryaman Prana Putra (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2024)
The hospital's obligation to carry out social functions as referred to in Article 2 paragraph (1) letter f. Corporate Social Responsibility (CSR) is an obligation for every hospital that is required to carry out its social functions. From the initial data obtained, the researcher saw that there were still some people who did not know about assistance from hospitals regarding CSR programs. This study aims to determine the implementation of Corporate Social Responsibility (CSR) management at TK.II Pelamonia Hospital Makassar.nThis study uses a descriptive qualitative method. The number of informants in the study were 5 people, namely 1 head of the cation service unit, 1 head of the PKRS unit and 3 people from the community around the TK.II Pelamonia Hospital Makassar. By determining the sample using purposive sampling technique. The research data was obtained through in-depth interviews with informants based on interview guidelines. The results of the research are presented in the form of statement quotes and narrations. The results of the research analysis of the implementation of Corporate Social Responsibility (CSR) management at TK.II Pelamonia Hospital Makassar, regarding planning, organizing, implementing, monitoring and evaluating have been carried out but there are several obstacles that occur in activities, but the obstacles obtained do not really affect the activities ( CSR).